Control of Bacterial Sulfite Detoxification by Conserved and Species-Specific Regulatory Circuits - Tan, Yi Jie Chelsea; Zhao, Chengzhi; Nasreen, Marufa; O’Rourke, Leo; Dhouib, Rabeb; Roberts, Leah; Wan, Ying; Beatson, Scott A.; Kappler, Ulrike (Frontiers in Microbiology, 2019)
Although sulfite, a by-product of the degradation of many sulfur compounds, is highly reactive and can cause damage to DNA, proteins and lipids, comparatively little is known about the regulation of sulfite-oxidizing enzymes (SOEs). Here we have investigated SOE gene regulation in two species of -Proteobacteria, Sinorhizobium meliloti and Starkeya novella, that degrade organo- and inorganic sulfur compounds, respectively, and contain unrelated types of SOEs that show different expression patterns. Our work revealed that in both cases, the molecular signal that triggers SOE gene expression is sulfite, and strong up-regulation depends on the presence of the sulfite-responsive, cognate ECF sigmafactor, making sulfite oxidation a bacterial stress response. In vitro experiments revealed overlapping regulation of SOEs by the respective RpoE1-like sigma factors, but in each species RpoE1 targeted different promoters (SnsorA, SmrpoE4) and was activated by different molecular signal, taurine (Sm) and tetrathionate (Sn), respectively and also differed in the magnitude of response generated. We therefore propose that RpoE1 is a secondary, species-specific regulator of SOE gene expression rather than a general, conserved regulatory circuit. Sulfite produced by major dissimilatory processes appeared to be the trigger for SOE gene expression in both species, as we were unable to find evidence for an induction of SOE activity in stationary growth phase. The basic regulation of bacterial sulfite oxidation by cognate ECF sigma factors is likely to be applicable to the three groups of alpha and beta-Proteobacteria in which we have identified similar SOE operon structures, as well as the absence of RpoE1 homologues in some cases.